Environmental sustainability, growth trajectory and gender : contemporary issues of developing economies - Chakraborty, Chandrima; Pal, Dipyaman (Emerald Publishing Limited, 2022)
Environmental Sustainability, Growth Trajectory and Gender focuses on three major issues affecting developing economies: environmental sustainability, growth trajectory and gender. The social, economic and environmental consequences of climate change and loss of essential ecosystems are becoming increasingly apparent. Within the global community, the challenges of sustainable development and gender equality are growing in importance. The knowledge and collective action of women would improve productivity, boost conservation of ecosystems and enhance economic growth in developing countries. Environmental Sustainability, Growth Trajectory and Gender provides a wealth of information for academic researchers, postgraduate students, and faculties of different disciplines, and will lead to increased awareness, policies and actions that will enhance gender equality and provide full enjoyment of sustainable development.